2009
DOI: 10.1088/0169-5983/41/5/051405
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal instability of a vortex ring computed by a vortex sheet panel method

Abstract: A Lagrangian panel method is presented for vortex sheet motion in threedimensional (3D) flow. The sheet is represented by a set of quadrilateral panels having a tree structure. The panels have active particles that carry circulation and passive particles used for adaptive refinement. The Biot-Savart kernel is regularized and the velocity is evaluated by a treecode. The method is applied to compute the azimuthal instability of a vortex ring, starting from a perturbed circular disc vortex sheet initial condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In addition to the mode number, figure 15 highlights that increasing the Richardson number of a vortex-ring interaction increases the maximum amplitude of the instability as well as the complexity (or structure) of the perturbations. In reference to figure 15[c], the structure of this instability is reminiscent of the numerical results found by Feng et al (2009) and Archer et al (2008) in the absence of stratification. Note that the instability appears to be all but absent in Stock et al (2008) for the numerical simulation of a vortex ring impacting a stratified interface.…”
Section: Three-dimensional Instabilitysupporting
confidence: 58%
“…In addition to the mode number, figure 15 highlights that increasing the Richardson number of a vortex-ring interaction increases the maximum amplitude of the instability as well as the complexity (or structure) of the perturbations. In reference to figure 15[c], the structure of this instability is reminiscent of the numerical results found by Feng et al (2009) and Archer et al (2008) in the absence of stratification. Note that the instability appears to be all but absent in Stock et al (2008) for the numerical simulation of a vortex ring impacting a stratified interface.…”
Section: Three-dimensional Instabilitysupporting
confidence: 58%
“…Examples of approaches of this type are found in vortex methods (e.g., Ref. [406]) and in vesicular flow problems (e.g., Ref. [407]), to mention just a few.…”
Section: Fast Methodologiesmentioning
confidence: 99%
“…Axisymmetric vortex rings formed along with a starting jet out of a circular nozzle are observed to ultimately become asymmetric. Feng et al numerically simulated the azimuthal instability for the ring and showed that the ring remains axisymmetric during early formation, but later on undergoes a wavy azimuthal instability [7]. Asymmetrization has been shown to be an indicator of performance and control of aircraft and other flight vehicles capable of extreme maneuvers [8].…”
Section: Introductionmentioning
confidence: 99%